An Approach To Study The Effects of GBP/USD Exchange Rate and Gold Prices on Brent Oil Prices Using Autoregressive Distributed Lag (ARDL) - Wstabdullah, Shaho Muhammad; Kamal, Muhammed Ali; Hamarashid, Hozan Khalid (Kurdistan Journal of Applied Research, 2023)
Autoregressive Distributed Lag (ARDL) is possible when cointegration analysis is applied to experimentally to shape the relationship between the variables without considering the regressors are stationary at its first difference or level, there is an integration of order one or both of the variables are mixed. Being based on one equation framework is a benefit of using the ARDL model, in order to take sufficient lags’ number and directing process data generation process in a modelling framework that goes from general to specific. The aim of this study is to focus on the trend of the relation between the GBP/USD rate and Brent Oil prices, which is done through the adoption of dependent variable which the oil price and the independent variable which is the dollar exchange rate. Another target of the research is to show the relationship between gold price and oil prices. The result shows that there are a number of likely influenced variable through by which the dollar-pound rate has effects on the demand and supply of oil as a result of its prices. That is done through the analysis of the relations between the variables of the study. Moreover, correlation coefficient values are given that there exists a positive explanatory correlation between the variables of the study. On the whole, there exists a positive long-term equilibrium relation between the GBP/USD exchange rate, price of oil and price of gold. Any change in the exchange rate of GBP/USD is causing the changes in prices of Brent oil.